A proposito di laicità. Una lunga e complessa storia semantica - Rosella Frasca (Firenze University Press, 2011)
The author, in her essay, describes the place occupied in the distant past of Western culture by the concept of secularism, and uses that are made. The author discovers the concept of secularism in ancient societies to bring it into modernity. He links it to issues related to youth education opportunities, training and multicultural issues. and it focuses on the concept of Citizenship and transmission of knowledge.